Bureaucratic Emotionalities: Managing Files, Forms, and Delays in the Canadian Spousal Reunification Process - Geoffrion, Karine (Anthropologica, 2021)
Based on an ethnographic study of Canadian women’s intimate relationships with a racialized man from the Global South, this article focuses on their experiences of the spousal reunification process. More specifically, I examine how the women emotionally and materially engage with spousal reunification procedures and administrative temporalities and how interactions with the Canadian immigration bureaucracy affect their subjectivity as women and citizens. I look at three embodied modes of involvement with bureaucratic procedures—waiting, working and fighting—each bringing forth its own set of emotions and creative coping strategies. I argue that love is central to the experience of the administrative procedures, as an ideological and technological tool used both by the state to regulate and discredit non-desirable relationships and by applicants to make sense of their position (of vulnerability) and to create meaningful narratives within state-imposed categories. A form of defensive agency emerges in women whose enormous application files, filled with “proof” of the authenticity of their relationship, shows how they have endorsed social anxieties about North-South intimacies and the strategies they have developed in order to legitimize their union.